2014
DOI: 10.1297/cpe.23.83
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Growth Hormone Treatment on Quality of Life in Japanese Children with Growth Hormone Deficiency: An Analysis from a Prospective Observational Study

Abstract: The aim of this study was to assess changes in quality of life (QoL) in Japanese children with GH deficiency (GHD) after 12 mo of GH treatment or with idiopathic short stature (ISS) after 12 mo without treatment. Children with GHD were treated with GH after enrollment. Outcome measures included the parent-rated Child Behavior Checklist (CBCL), the Youth Self-Report Form (YSR), and height standard deviation scores (SDS). Total CBCL scores significantly decreased in children with GHD (n = 152, mean change (stand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 16 publications
2
9
0
4
Order By: Relevance
“…Another source of concern is that reported apparent HRQOL ‘measures’ are actually detecting behavioural variations. Tanaka et al reported the effect of GHT in children with ISS and GHD but the tools used (CBCL and YSR) actually only evaluate deviations in behaviour patterns from reported norms and do not measure HRQOL itself. Taback & van Vliet used an adult HRQOL tool (SF36) in adolescent girls with Turner syndrome, but not a child and adolescent age‐specific measure.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Another source of concern is that reported apparent HRQOL ‘measures’ are actually detecting behavioural variations. Tanaka et al reported the effect of GHT in children with ISS and GHD but the tools used (CBCL and YSR) actually only evaluate deviations in behaviour patterns from reported norms and do not measure HRQOL itself. Taback & van Vliet used an adult HRQOL tool (SF36) in adolescent girls with Turner syndrome, but not a child and adolescent age‐specific measure.…”
Section: Discussionsupporting
confidence: 72%
“…Chaplin et al claimed an effect of GHT in short prepubertal children, but did not provide control group comparisons . More recently, a cohort of Japanese GHD children found significant correlations between GH‐induced growth in self‐reported measure of HRQOL in in line with earlier findings by Stabler et al, but there was no correlation with parent‐rated HRQOL scores and catch‐up growth. Unfortunately, there was no age‐matched control group, and the mean age and age distributions were significantly different between the GHD and ISS groups.…”
Section: Introductionmentioning
confidence: 99%
“…В настоящее время подобного рода исследования в России не представляются возможными, так как национальных данных об уровне качества жизни у детей с ДГР или изменении этого уровня на фоне терапии не существует. Для проведения подобных исследований требуется создание соответствующих опросных листов для данной группы пациентов или адаптация уже имеющихся и используемых в зарубежной практике анкет к российским реалиям, как, например, было сделано в Японии [10].…”
Section: экономическая эффективность применения ргр у детейunclassified
“…Исследователи в Японии использовали «контрольный список поведения ребенка» (child behavior checklist -CBCL) и «анкету самоотчета для подростков» (youth self report, YSR) -системы оценки, разработанные еще в 60-е годы XX века и основанные на эмпирическом опыте по Ахенбаху [23]. Важно отметить, что для данного исследования обсуждаемые списки были переведены на японский язык и адаптированы для Японии.…”
Section: качество жизни пациентов с дефицитом гормона ростаunclassified
“…Так, T. Tanaka и соавт. [23] говорят об изменении качества жизни детей и подростков в положительную сторону в зависимости от изменения SDS роста (в сторону улучшения показателя) за время лечения препаратами рГР в течение одного года. Интересен и тот факт, что в данном случае, так же как в предыдущем, изначальные показатели качества жизни у детей с ДГР были вполне удовлетворительны в сравнении с детьми с диагнозом «идиопатическая низкорослость».…”
Section: качество жизни пациентов с дефицитом гормона ростаunclassified